Dealuminasi Zeolit Daerah Moncongloe Kabupaten Maros Provinsi Sulawesi Selatan Dengan Menggunakan Asam Sulfat (Jurnal Geomine, 2022)
Zeolite is a hydrated aluminosilicate mineral that possesses pore structures to be used as an absorbent material. These absorbent properties of zeolite are useful in the adsorption of toxic materials such as ammonium and heavy metals. It can therefore be used as additives in livestock, shrimp farming, wastewater treatment, and palm oil refining. However, the commonly used natural zeolite has a low Si/Al ratio and higher impurities. It can therefore reduce the absorption capability. One of the activation methods of zeolite is chemical dealumination; that is removal of Al from crystal structures of zeolite to increase its Si/Al ratio. This research aimed to find out the mineralogical and chemical composition of zeolite samples. Dealumination experiments were then carried out using sulfuric acid as a solvent with acid concentration and temperature as experimental variables. Results of the analysis show that zeolite contains feldspar, clinoptilolite, mordenite, and quartz. The chemical composition of zeolite was dominated by SiO2 and Al2O3. The experiment indicates Si/Al ratio was increased from 1.09 to 1.29, which was achieved at an H2SO4 concentration of 1.5 M with a temperature of 100oC.